Alterações hepáticas em cães intoxicados experimentalmente por sementes de Crotalaria spectabilis - Bellodi, Carolina [UNESP] (2014)
The poisoning of pasture weeds cause huge losses in Brazilian cattle, usually occurs because the spontaneous ingestion of the plant in pastures of poor quality due to drought, frost or fire. Animals can also become contaminated accidentally by contamination of grain used in the diet of large animals. Plants of the genus Crotalaria sp. have an active ingredient that induces liver cirrhosis in animals and their seeds commonly blend the grains during mechanical harvesting. No study has been done with pets relating the quality of feed offered to them. The susceptibility of experimental dog model as a framework to poisoning Crotalaria spectabilis seeds, as well as to verify whether proliferation of hepatic fibrosis and hepatic stellate cells in the liver of dogs receiving different concentrations of plant seeds (G1 - 0, 2 % , G2 - 0.4 % and G3 - 0.6 % ) , in zero time (baseline control ), T14 days and T28 days were the goals of these studies . The liver samples were obtained by biopsy guided by ultrasound, with the animals under anesthesia. Fibrosis was evaluated by histochemical methods (Gordon and Sweet, Masson Trichrome and Picrosirius) and the density of hepatic stellate cells was evaluated by immunohistochemistry. The livers of animals in groups G1 and G2 showed no increase in reticulin or collagen fibers in T14 and T28. In G3 showed mild fibrosis, predominantly in T28. We conclude that the experimental poisoning of dogs by Crotalaria spectabilis seeds a proliferation of hepatic stellate cells in the initial phase occurs, followed by fibrosis and reduction in this cell population, confirming the role of these cells in repair of liver tissue